Parque del Rio: Planificación de espacios públicos vinculados a la estructura ecología principal del municipio de Pitalito, Huila - Rincón López, Juan Diego (Universidad Antonio Nariño, 2024)
The spaces for recreation, use and urban development are made up of existing public spaces and created in the city to meet the urban dynamics, the free development of its inhabitants, the impro-vement of their quality of life, among others, is a direct responsibility of the state, of individuals through suitable legal and planning figures, as well as of the citizens who interact in the territory as such. These spaces are designated and used as strategic points for the development of individual or collective activities that consolidate the city, generating identity, dynamism, well-being and satisfaction among the citizens residing in the sector and the community in general that benefits from them, in the city of Pitalito there has been a clear lack of planning and intervention planningthat seeks the endowment, creation and integration of public spaces useful to the city, among the different classes of the aforementioned spaces we find: Public Parks, Zonal Parks, Neighborhood Parks, squares, central park, sports venues and public spaces for human interaction , so that in this way it transcends the city.